"Merged-chelating" approach for constructing high-spin Mn aggregate: A [MnIII2] dimer and a 2-D honeycomb network based on star-shaped [MnIIMnIII3] tetramer. (1st July 2018) - Bai, Jiaquan; Yang, Chao; Li, Guanghua; Bi, Yanfeng; Li, Xiaolei; Tang, Jinkui; Han, Tian; Zheng, Yan-Zhen; Wu, Gang; Qiu, Shilun
Graphical abstract: Pyridin-2-ylmethanol and 1, 3-propanediol are merged into one framework resulting in a new tridentate ligand. Its initial attempt harvested a Mn III dimer and a 2-D honeycomb network based on star-shaped [Mn II Mn III 3 ] tetramer. Magnetic studies revealed dominant ferromagnetic interactions within the Mn III dimer and the star-shaped [Mn II Mn III 3 ] tetramer unit. Abstract: Pyridin-2-ylmethanols (hmp) and 1, 3-propanediols have been proven to be successful ligands for constructing high-spin manganese clusters. In this work, both ligands are merged into one framework, resulting in a new tridentate ligand 4-chloro-2-(hydroxy(pyridin-2-yl)methyl)phenol. Its initial attempt in Mn coordination chemistry harvested a Mn III dimer [Mn III 2 (L)2 (AcAc)2 ] and a 2-D honeycomb network based on star-shaped [Mn II Mn III 3 ] tetramer [Mn II Mn III 3 (Na)1.5 (L)6 ](OH)0.5 ·(MeOH)1.5 n . The two clusters were characterized by single crystal X-ray diffraction, IR spectra, elemental analysis, and magnetic measurements. Magnetic studies revealed dominant ferromagnetic interactions within the Mn III dimer and star-shaped [Mn II Mn III 3 ] tetramer unit.